PUMICE LAYER: A SOLUTION TO DIMINISH THERMAL ON HORIZONTAL LEFTOVER PLACE IN ROOFTOP - Danny Santoso Mintorogo; Wanda Widigdo; Anik Juniwati (DIMENSI (Journal of Architecture and Built Environment), 2019)
There are many ways to solve thermal on buildings, such as the installation of horizontal and vertical sun-shading devices on four-direction facades. However, rooftops are often ignored. In low-rise to high-rise buildings’ rooftop, there are leftover places exposed to solar heat radiation all day. Some rooftop places are equipped with polymer thermal roof insulation, and some are even without outer thermal insulation. The research aims to find a solution to diminish the horizontal thermal radiation by using eco-friendly material, pumice, as an outer thermal insulation. Exploiting method was used on one roof model as a conventional rooftop (without outer insulation), and another as a modified rooftop model covered with pumice. Couple HOBO data logger U12-012 temperature sensors were used to measure rooftop surface temperatures and room model temperatures. Results show that the thermal radiation were blocked efficiently: 26oC on pumice covered rooftop. It saved 8.4oC room temperature.